Regional price differences in urban China 1986 -2001: estimation and implication - Cathy Honge Gong; Xin Meng (Institute for the Study of Labor (IZA), 2008)
Despite the intensive efforts made by economists to examine regional income inequality in China, limited attention has been paid to disentangle the contribution of regional price differentials. This paper examines regional price differential in urban China over the period 1986 to 2001. Spatial Price Index (SPI) is normally calculated using the Basket Cost Method, which defines a national basket and measures price variation of this common basket across different regions. The weakness of this method is that it arbitrarily assumes consumers' preferences and has a strong reliance on good regional level price data, which are often not available. This paper adopts the Engel's curve approach to estimate a Spatial Price Index for different provinces. The SPI obtained from the Engel's curve approach indicates larger regional price variations than those obtained from the Basket Cost method. Further, regional price variations in urban China increased significantly during the late 1980s to early 1990s, stabilized at a relatively high level during the mid to end 1990s. Adjusting for the regional price variations our finding suggests that regional income inequality increased the most between the late 1980s and early 1990s, and stabilized in the mid 1990s, which contradicts previous findings using unadjusted income.
Keywords: C43; 330; Spatial price index; Engel's curve; income inequality; China; Regionale Preisstruktur; Preisindex; Mikroökonomische Konsumfunktion; Regionale Einkommensverteilung; Stadtregion; China